Динаміка рухових порушень, викликаних гіпоксією мозку, за умов електричного подразнення (ЕП) палеоцеребелярної кори мозочка = The dynamic of locomotor disturbances, induced via hypoxic damage of the brain, under conditions of electrical stimulations (ES) of the paleocerebellar cortex - Nenova, O. M. (Journal of Education, Health and Sport, 2015)
Nenova O. M. Динаміка рухових порушень, викликаних гіпоксією мозку, за умов електричного подразнення (ЕП) палеоцеребелярної кори мозочка = The dynamic of locomotor disturbances, induced via hypoxic damage of the brain, under conditions of electrical stimulations (ES) of the paleocerebellar cortex. Journal of Education, Health and Sport. 2015;5(12):581-587. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.44263 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A581-587 http://pbn.nauka.gov.pl/works/687225 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.12.2015. Revised 15.12.2015. Accepted: 29.12.2015. УДК: 612.826+612.8.-009 ДИНАМІКА РУХОВИХ ПОРУШЕНЬ, ВИКЛИКАНИХ ГІПОКСІЄЮ МОЗКУ, ЗА УМОВ ЕЛЕКТРИЧНОГО ПОДРАЗНЕННЯ (ЕП) ПАЛЕОЦЕРЕБЕЛЯРНОЇ КОРИ МОЗОЧКА THE DYNAMIC OF LOCOMOTOR DISTURBANCES, INDUCED VIA HYPOXIC DAMAGE OF THE BRAIN, UNDER CONDITIONS OF ELECTRICAL STIMULATIONS (ES) OF THE PALEOCEREBELLAR CORTEX О. М. Нєнова O. M. Nenova Одеський національний медичний університет, Одеса Odessa National Medical University, Odessa Summary In Wistar rats the bilateral ligation of common arterii carotici served as a model of hypoxic damage of brain. It was established that ES (100 Hz) of paleocerebellar cortex (nodulus, uvula) was followed by the reduction of the lethality of animals, increasing of the period of preserved pain susceptibility along with the ability to maintain the vertical posture and static reflexes. Low- frequency ES (10 Hz) was less effective with regard to retardation of hypoxic- induced locomotor disturbances. Ключові слова: paleocerebellar cortex, electrical stimulation, brain hypoxic damage. Резюме У щурів лінії Вістар білатеральною перев’язкою загальних сонних артерій викликали гіпоксичне ушкодження мозку. ЕП (100 Гц) палеоцеребелярних відділів (nodulus, uvula) супроводжувалось зменшенням летальності тварин, збільшенням періоду збереження больової чутливості, утримування в вертикальному положенні і збереження статичних рефлексів. Менш ефективною було низькочастотне ЕП (10 Гц) палеоцеребелярної кори. Ключові слова: палеоцеребелярна кора, електричне подразнення, гіпоксичне ураження мозку. Резюме ДИНАМИКА ДВИГАТЕЛЬНЫХ НАРУШЕНИЙ, ВЫЗВАННЫХ ГИПОКСИЕЙ МОЗГА В УСЛОВИЯХ ЭЛЕКТРИЧЕСКОЙ СТИМУЛЯЦИИ (ЭС) ПАЛЕОЦЕРЕБЕЛЛЯРНОЙ КОРЫ МОЗЖЕЧКА. У крыс линии Вистар билатеральной перевязкой общих сонных артерий вызывали гипоксическое поражение мозга. ЭС (100 Гц) палеоцеребеллярных отделов коры (nodulus, uvula) сопровождалась уменьшением летальности животных, увеличением периода сохранения болевой чувствительности, удерживания вертикального положения и сохранения статических рефлексов. Менее эффективной была низкочастотная ЭС (10 Гц) палеоцеребеллярной коры. Ключевые слова: палеоцеребеллярная кора, электрическая стимуляция, гипоксическая травма мозга.